Análise comparativa das técnicas de MPPT, P&O, Sliding Mode e Backstepping aplicadas a sistemas fotovoltaicos - Silva, Robson Taveira Gonçalves da (2020)
Photovoltaic systems have the characteristic of converting solar energy into electrical energy, but the efficiency of the conversion depends largely on environmental conditions such as irradiation and temperature in the photovoltaic cells. This work presents analises, in computer simulation, of three techniques that aim the search of the Maximum Power Point Tracking (MPPT) of the PV system. The studied techniques are: disturb and observe P&O, Sliding Mode Control (SMC) and Backstepping control. For the analyzes, two types of systems were adopted, with power variation applied in each one. The first system has an array parallel connected PV modules with a total power of 110 W, the second arrangement has four modules in parallel with a total of 220 W. In both arrangements, a shading effect was simulated, so that the MPPT techniques response for the system power variation and the shading effect could be observed. Connecting the modules to a resistive load, a static DC-DC converter was used. The selected topology was the classic Boost, as it presents the characteristic of tension elevation. At the end of the analysis it can be observed that the P&O algorithm obtained the lowest values of extracted power in all system combinations, SMC was advantageous in the lower power system, while Backstepping had the best response in power transients and higher power extraction in the higher power system. Due to its better performance, the Backstepping technique was applied to a high gain DC-DC